2017
DOI: 10.1111/joa.12621
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and evolution of the oral shield in marsupial neonates including the newborn monito del monte (Dromiciops gliroides, Marsupialia Microbiotheria) pouch young

Abstract: Newborn marsupials can be arranged into three grades of developmental complexity based on their external form, as well as based on their organ systems and their cytology. The dasyurids are considered the least developed marsupials at birth, while didelphids and peramelids are intermediate, and macropods are the most developed. Currently there is still little information on caenolestid and microbiotherid development at birth. Developmental stages can be graded as G1, G2 and G3, with G1 being the least developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 95 publications
(233 reference statements)
0
9
0
Order By: Relevance
“…The nares are of large size and round shape, with nasal swellings surrounding them. Distinct organs of the anterior nose region are not yet present; the specific structures of the rhinarium develop later ([ 65 ], this study).…”
Section: Discussionmentioning
confidence: 99%
“…The nares are of large size and round shape, with nasal swellings surrounding them. Distinct organs of the anterior nose region are not yet present; the specific structures of the rhinarium develop later ([ 65 ], this study).…”
Section: Discussionmentioning
confidence: 99%
“…To date, most of the studies investigating the role of developmental constraints on morphological evolution in mammals focus either on marsupials [12,14,15,20], or placentals [21]. A handful of studies have included a broad sample of placental and marsupial mammals [8,16,19], and focused on the limb elements [7,12,16,22,23] or the skull, but none have focused on the morphological evolution of the jaw, the one structure that is uniformly and unambiguously functioning in neonatal marsupials.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this accelerated gestation, marsupials give birth to neonates in an embryonic condition, which then need to travel from the birth canal powered by their forelimbs, in order to attach to the mother's teat to suckle [ 11 ]. Because of these early functional requirements, the morphology of newly born marsupials is a mosaic of structures that develop early (such as the forelimb [ 7 , 8 , 12 , 13 ] and oral apparatus [ 14 , 15 ]) and late (such as the hind limbs and braincase [ 8 , 12 , 13 , 16 ]). Consequently, the functional requirements imposed by this distinctive reproductive mode may have constrained the evolution of marsupials and cause their relatively low diversity and reduced morphological variation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it would be naive to assume that monitos are monotypic, genetically homogeneous, or morphologically undifferentiated. This species, despite having been recognized as emblematic for science several decades ago because of its role as a disperser, its relict condition, and its phylogenetic affinities with Australian marsupials, began to be studied in a comprehensive way only a few years ago (e.g., Schneider andGurovich 2017, Gurovich andAshwell 2020). These studies showed that Dromiciops varies both in external and in cranial morphology, showing a strong genetic structuration across its range, with important particularities in islands and other isolated populations (D'Elia et al 2016, Valladares-Gómez et al 2017, Valladares-Gómez et al 2019J.…”
Section: Discussionmentioning
confidence: 99%